Community-based program to increase use of hearing conservation practices among farm and rural youth: a cluster randomized trial of effectiveness - McCullagh, Marjorie C. (BMC Public Health, 2020)
BACKGROUND: Noise exposure and associated hearing loss affects an estimated 2 million farm youth who are exposed as farm residents, farm family workers, hired workers, children of migrant or seasonal workers, and farm visitors. Risk factors for farm youth include frequent exposure to high farm noise; farm work from an early age, and exposure to high recreational noise (e.g., firearms, ATVs, and personal listening devices). METHODS: This study compared the effectiveness of two interventions and control. The programs included a community-based interactive youth educational program alone (Group A), a community-based interactive youth educational program followed by an Internet-based booster (Group B), and a no-interaction control (Group C). The study used a cluster randomized control design, with equal allocation ratio to each cluster, without blinding. Inclusion criteria included enrollment in grade 4, parental consent, English speaking, and attending a community-based educational event included in the cluster sampling. A total of 1979 youth were enrolled at 36 sites distributed across the 3 study arms in the following distribution: N = 662 in 13 sites (Group A), N = 680 in 12 sites (Group B), and N = 637 in 11 sites (Group C). RESULTS: Comparison with pre-intervention data showed no difference in intent to use hearing conservation strategies in experimental groups. However, knowledge and attitudes toward hearing conservation were improved in the groups receiving the Internet-based booster. Participants reported frequent exposure to sources of hazardous noise (e.g., loud sporting events, firecrackers, personal listening devices). CONCLUSIONS: It is feasible and acceptable to incorporate hearing health education into an already existing system designed to deliver health and safety educational programming to farm and rural youth. The program was adopted by the partner agency for dissemination to up to 100,000 youth annually. Results of this study inform future intervention studies, interventions aimed at farm youth, and interventions to increase use of hearing conservation strategies, as well as offer a base for developing programs for non-English speaking children. TRIAL REGISTRATION: Clinicaltrials.gov registration CT02472821. Date of trial registration: 06/09/2015 (retrospectively registered).